2006
DOI: 10.1016/j.ydbio.2005.11.011
|View full text |Cite
|
Sign up to set email alerts
|

WNT/β-catenin pathway up-regulates Stat3 and converges on LIF to prevent differentiation of mouse embryonic stem cells

Abstract: Embryonic stem (ES) cells rely on growth factors provided by feeder cells or exogenously to maintain their pluripotency. In order to identify such factors, we have established sub-lines of STO feeder cells which exhibit variable ability in supporting ES cell self-renewal. Functional screening identifies WNT5A and WNT6 as STO cell-produced factors that potently inhibit ES cell differentiation in a serum-dependent manner. Furthermore, direct activation of beta-catenin without disturbing the upstream components o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
208
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 264 publications
(220 citation statements)
references
References 48 publications
9
208
2
1
Order By: Relevance
“…Furthermore, several studies, including ours, suggest that β-catenin plays an important role in the self-renewal of ES cells [12,13]. Establishment of β-catenin-null ES cells, however, has also been reported [23].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Furthermore, several studies, including ours, suggest that β-catenin plays an important role in the self-renewal of ES cells [12,13]. Establishment of β-catenin-null ES cells, however, has also been reported [23].…”
Section: Discussionmentioning
confidence: 73%
“…It is reported that activation of β-catenin leads to induction of STAT3 mRNA in ES cells [12]. Involvement of c-myc, a direct target molecule of β-catenin, in the self-renewal of ES cells has been demonstrated [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2f). Therefore elevated c-Myc is not necessary for ES-cell propagation, although some requirement for basal Myc activity is not excluded.STAT3 signalling is central to previous models of ES-cell self-renewal 8,21 and has also been implicated in effects of BIO 20,22,23 . In 3i, however, we do not detect activation of STAT3 or induction of its target SOCS3 (Supplementary Information).…”
mentioning
confidence: 99%
“…STAT3 signalling is central to previous models of ES-cell self-renewal 8,21 and has also been implicated in effects of BIO 20,22,23 . In 3i, however, we do not detect activation of STAT3 or induction of its target SOCS3 (Supplementary Information).…”
mentioning
confidence: 99%